Pengembangan Media Fun Thinkers Book Berbasis Saintifik untuk Meningkatkan Pemahaman Konsep Energi Kelas IV - Ayuni, Ramadyani Saskya; Heryanto, Dwi; Saputri, Aprilia Eki (Jurnal Didaktika Pendidikan Dasar, 2025)
The background of this study is the low level of understanding of fourth-grade students at an elementary school in Tasikmalaya Regency regarding energy and its changes. This study aims to develop and measure the effectiveness of the Fun Thinkers Book media on the conceptual understanding of fourth-grade elementary school students. The method used in this study is a mixed method with the ADDIE development model, namely, analysis, design, development, implementation, and evaluation. The research population consists of fourth-grade elementary school students in Tasikmalaya Regency, with a sample size of all fourth-grade students totalling 12 individuals, using a saturated sampling technique. The analysis techniques used in this study were quantitative data analysis using a Likert scale and qualitative data analysis. The average validation results from subject matter experts, media experts, and learning practitioners placed the media in the “highly suitable” category with a percentage of 91.4%. The results of the students' tests before and after using the media showed an improvement with an N-Gain value of 0.76, which falls into the “high” category. Therefore, the Fun Thinkers Book media is deemed highly suitable for use and effective in enhancing fourth-grade elementary school students’ understanding of energy concepts and their transformations.